KINESIOLOGY- THE SCIENCE OF MOVEMENT In Relation to Education, Hygiene and Therapy. A piece of the legacy of Nicolas Dally (1795-1862) for contemporary kinesiology scholars and professionals - Prot, Franjo (Annales Kinesiologiae, 2015)
Kinesiology has recently gained full worldwide credibility as an academic discipline in the field of human movement and exercise practice in the area of education, sport, recreation and kinesitherapy, becoming a proper denominator for the field of sport or exercise science. It seems almost compulsory that on the occasion of the introduction of the first issue of Annales Kinesiologiae, a new scientific journal in the field, to remember and speak about Nicolas Dally and his work. In this paper a short biography of the forefather of KINESIOLOGY, or CINÉSIOLOGIE, will be presented as well as how Dally introduced the term and the concept in his book from 1857. It is presented and integrated with some newly available illustrative material. Dally’s bibliography based on resources of worldwide relevant library catalogues is added to the references.